Kinerja Pertumbuhan dan Kelulushidupan Benih Ikan Mas Sinyonya dengan Pakan Hormon Pertumbuhan Rekombinan - Fadhila, Ridwan; Hermawan, Dodi; Putra, Achmad Noerkhaerin; Saifullah, Saifullah (Jurnal Akuakultur Sungai dan Danau, 2024)
Cyprinus carpio Linnaeus is a leading commodity for cultivation in Pandeglang Regency, Banten Province. One of the hormones that can stimulate fish growth is the recombinant Epinephelus lanceolatus growth hormone (rElGH) in artificial feed. The research aimed to determine the optimal dose of rElGH used in artificial feed on the growth and survival of Sinyonya. The common carp of Sinyonya initial weight of 2 g was reared in an aquarium with volume 72 L. The research design used was completely randomized design with four treatments, namely (A) control, (B) rElGH 3 mg/kg, (C) rElGH 6 mg/kg, and (D) rElGH 9 mg/kg and each treatment consisted of three replications. The results showed that the absolute weight of Sinyonya carp juvenile treated with treatment B produced the best biomass of 3.22±0.06 g, treatment C 3.14±0.05 g, treatment D 3.04±0 .08 g, and treatment A 2.62±0.06 g.  The best survival rate in treatment B was 100%, treatment C 97.67%, treatment D 97.67%, and treatment A 93.33%. The feed consumed by treatment A 199.27 g, treatment B was 196.07 g, treatment C was 194.77 g, and treatment D was 195.33 g. The specific growth rate of treatment A 7.49%, treatment B 9.12%, treatment C 8.97%, and treatment D 8.69%. The feed conversion ratio for treatment B is 4,10%, treatment C 4.,16%, treatment D 4,32, and treatment A 5.,24% . The addition of rElGH to feed resulted in better growth and survival compared to the control treatment. Feeding with rElGH 3 mg/kg for 35 days was able to improve growth performance in the common carp Sinyonya.